Retinal long term neuroprotection by Cerium Oxide nanoparticles after an acute damage induced by high intensity light exposure. (May 2019) - Tisi, A.; Passacantando, M.; Lozzi, L.; Riccitelli, S.; Bisti, S.; Maccarone, R.
Abstract: Cerium Oxide nanoparticles are antioxidant agents with autoregenerative radical scavenging activities, effective in preventing degeneration of photoreceptors of an albino rat when intravitreally injected prior to exposure to high intensity light. In this study, we performed a post injury administration of nanoceria and a long term analysis of their neuroprotective properties in order to better simulate the therapeutic treatment as it is carried out on patients with age related macular degeneration, and while photoreceptor degeneration is ongoing. We also injected nanoceria labelled with fluorescein isothiocianate in order to analyze their persistence after a single administration in a damaged retina and to investigate how long they both maintain their neuroprotective properties and where they localize in the retina. We demonstrated that after a single intravitreal injection, nanoceria remained in the retina for a long time and retained their neuroprotective properties. All these data form excellent bases for future clinical applications. Highlights: Nanoceria are effective when injected seven days after retinal damage induction. Nanoceria stay in the damaged retina for at least 60 days. A single nanoceria administration is enough to protect the retina until two months. Nanoceria protect in terms of visual function, morphology and inflammation.